2017
DOI: 10.1002/ajhb.23005
|View full text |Cite
|
Sign up to set email alerts
|

Lower face asymmetry as a marker for developmental instability

Abstract: The findings suggest that lower face asymmetries are a marker for environmental stress and cerebral lateralization during early development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
4
10
0
Order By: Relevance
“…Unilateral retrognathia was more common than unilateral prognathia (~17% and ~8%, respectively). Interestingly, the former display FA while the later displays DA, occurring more often on the left than the right side . The authors also found that the prevalence of symmetric, that is bilateral retrognathia and prognathia, changes with age.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Unilateral retrognathia was more common than unilateral prognathia (~17% and ~8%, respectively). Interestingly, the former display FA while the later displays DA, occurring more often on the left than the right side . The authors also found that the prevalence of symmetric, that is bilateral retrognathia and prognathia, changes with age.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have indicated that the mandible displays significant asymmetry. Hujoel et al evaluated lower face asymmetry in ~6500 adolescents, utilizing dental markers as a surrogate for jaw size. They reported lower face asymmetry in ~25% of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers such as low birth weight may not only reflect information on early life stressors, but may also reflect inherited characteristics (Hujoel et al 2017). Therefore, identification of alternative measures of early childhood experience (beyond birth weight and growth stunting), particularly those that capture the source and timescale of early childhood exposures, are a priority for research on the DOHaD (Kuzawa 2005b; Newnham and Ross 2009; Kuzawa and Quinn 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bioarchaeologists identified mandibular DA in an early medieval sample from the Czech Republic, potentially related to diet and chewing habits (Ibrova et al, 2017). In a recent population, DA of the lower face was associated with environmental stress (Hujoel et al, 2017). An investigation of a contemporary population of highly inbred Bedouin adults quantified DA in the calvarium and cranial base DA (Hershkovitz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%